Kir6.1, a component of an ATP-sensitive potassium channel, regulates natural killer cell development - Samper, Natalie; Hardardottir, Lilja; Depierreux, Delphine M.; Song, Soomin C.; Nakazawa, Ayano; Gando, Ivan; Nakamura, Tomoe Y.; Sharkey, Andrew M.; Nowosad, Carla R.; Feske, Stefan; Colucci, Francesco; Coetzee, William A. (Frontiers in Immunology, 2024)
IntroductionInvolved in immunity and reproduction, natural killer (NK) cells offer opportunities to develop new immunotherapies to treat infections and cancer or to alleviate pregnancy complications. Most current strategies use cytokines or antibodies to enhance NK-cell function, but none use ion channel modulators, which are widely used in clinical practice to treat hypertension, diabetes, epilepsy, and other conditions. Little is known about ion channels in NK cells. ResultsWe show that Kcnj8, which codes for the Kir6.1 subunit of a certain type of ATP-sensitive potassium (KATP) channel, is highly expressed in murine splenic and uterine NK cells compared to other K+ channels previously identified in NK cells. Kcnj8 expression is highest in the most mature subset of splenic NK cells (CD27-/CD11b+) and in NKG2A+ or Ly49C/I+ educated uterine NK cells. Using patch clamping, we show that a subset of NK cells expresses a current sensitive to the Kir6.1 blocker PNU-37883A. Kcnj8 does not participate in NK cell degranulation in response to tumor cells in vitro or rejection of tumor cells in vivo, or IFN-γ release. Transcriptomics show that genes previously implicated in NK cell development are amongst those differentially expressed in CD27-/CD11b+ NK cells deficient for Kcnj8. Indeed, we found that mice with NK-cell specific Kcnj8 gene ablation have fewer CD27-/CD11b+ and KLRG-1+ NK cells in the bone barrow and spleen. DiscussionThese results show that the KATP subunit Kir6.1 has a key role in NK-cell development.